Amalgamating Provincial Health Authorities: Assessing the Experience of Nova Scotia - Katherine Fierlbeck (McMaster University Library Press, 2019)
Reflecting the shift away from regionalized health governance in Canada's provinces, the Nova Scotia government consolidated its nine Distinct Health Authorities into the single Nova Scotia Health Authority as of 1 April 2015. Regionalized health administration had originally been expected to produce economic efficiencies but, after two decades, a fragmented system of health governance was increasingly perceived as inflexible, uneven, and expensive. A more centralized system was presented as a means of reducing administrative costs, promoting scale economies, allowing greater flexibility, and facilitating standardization, which would in turn lead to significant savings. Five years on, however, the expected cost savings have not materialized. While there has been more success in standardization of services, not all attempts at standardization have led to greater efficiency. Evidence for greater flexibility is mixed. Problems with amalgamating health authorities include opportunity costs incurred by thoroughgoing reform, ambiguous and diminished accountability, administrative bottlenecks, decreased responsiveness, and poor working relationships with health care professionals leading to issues of access to health care services.